CASTING A NEW CANON: COLLECTING AND TREATING CASTS OF GREEK AND ROMAN SCULPTURE, 1850–1939. (December 2019) - Payne, Emma M.
Abstract : From the mid-nineteenth century, it became de rigueur for Classics Departments to acquire casts of Greek and Roman sculpture to form reference and experimental collections. Recent scholarship has revived such casts, investigating their role as instruments of teaching and research, and their wavering popularity. This paper further examines the aims of those responsible for collecting casts, and discusses how these objectives influenced their materiality and treatment, as well as showing how the de facto creation of a new canon of casts through their repetition across the collections of different institutions contributed to the decline in their perceived importance.